2013
DOI: 10.1055/s-0033-1353393
|View full text |Cite
|
Sign up to set email alerts
|

Glanzmann Thrombasthenia: State of the Art and Future Directions

Abstract: Glanzmann thrombasthenia (GT) is the principal inherited disease of platelets and the most commonly encountered disorder of an integrin. GT is characterized by spontaneous mucocutaneous bleeding and an exaggerated response to trauma due to platelets that fail to aggregate when stimulated by physiologic agonists. GT is caused by quantitative or qualitative deficiencies of αIIbβ3, an integrin coded by the ITGA2B and ITGB3 genes and which by binding fibrinogen and other adhesive proteins joins platelets together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 125 publications
1
33
0
1
Order By: Relevance
“…The molecular characterization of patients revealed 16 mutations (half of them not reported previously) along both genes encoding for the α IIb β 3 receptor: 11 mutations were located in the ITGA2B gene within 8 patients (3 of them were compound heterozygous) and 5 in the ITGB3 in 4 more patients. According to a regularly updated database ( http://sinaicentral.mssm.edu/intranet/research/glanzmann ), and to what has been previously stated [ 15 ], we observed more mutations affecting ITGA2B possibly because, although a smaller gene than ITGB3 , it has 30 exons (and double number of splice sites) compared to 15 in ITGB3 . In patient GT-12, who has unequivocally been diagnosed by functional studies as GT, no mutations were detected.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The molecular characterization of patients revealed 16 mutations (half of them not reported previously) along both genes encoding for the α IIb β 3 receptor: 11 mutations were located in the ITGA2B gene within 8 patients (3 of them were compound heterozygous) and 5 in the ITGB3 in 4 more patients. According to a regularly updated database ( http://sinaicentral.mssm.edu/intranet/research/glanzmann ), and to what has been previously stated [ 15 ], we observed more mutations affecting ITGA2B possibly because, although a smaller gene than ITGB3 , it has 30 exons (and double number of splice sites) compared to 15 in ITGB3 . In patient GT-12, who has unequivocally been diagnosed by functional studies as GT, no mutations were detected.…”
Section: Discussionsupporting
confidence: 78%
“…Presented information includes data from the “Functional and Molecular Characterization of Patients with Inherited Platelet Disorders” a collaborative project that was undertaken under the scientific sponsorship of the Spanish Society of Thrombosis and Hemostasis. The main part of this manuscript focuses on describing our findings from patients diagnosed with two severe autosomal recessive IPDs affecting the platelet adhesion and aggregation, BSS and GT respectively [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…During activation, platelets undergo a shape change following activation of GPIIb/IIIa, which creates the foundation for platelet aggregation and formation of a platelet plug [9] . The importance of GPIIb/IIIa activation is demonstrated in patients suffering from Glanzmann's thrombasthenia whose platelets fail to aggregate due to a lack of functional GPIIb/IIIa, causing excessive hemorrhage after trauma or surgery [12] . PAC-1 binds to activated GPIIb/IIIa and, in the present study, the increased PAC-1 binding after LBNP demonstrates that platelets were activated and that their aggregation ability was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a general bleeding disorder in GT patients, bleeding severity differs considerably between affected individuals, even within the same family or ethnic group [ 39 ]. Understanding the molecular basis leading to this high phenotypic variability is subject of intensive research [ 40 ]. However, the scattered geographic distribution of patients with rare platelet diseases such as Glanzmann thrombasthenia impedes frequent clinical contact and scientific workflow even in specialized centers.…”
Section: Discussionmentioning
confidence: 99%